2018
DOI: 10.3201/eid2402.170778
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Respiratory Disease Associated with Human Rhinovirus C in Wild Chimpanzees, Uganda, 2013

Abstract: We describe a lethal respiratory outbreak among wild chimpanzees in Uganda in 2013 for which molecular and epidemiologic analyses implicate human rhinovirus C as the cause. Postmortem samples from an infant chimpanzee yielded near-complete genome sequences throughout the respiratory tract; other pathogens were absent. Epidemiologic modeling estimated the basic reproductive number (R0) for the epidemic as 1.83, consistent with the common cold in humans. Genotyping of 41 chimpanzees and examination of 24 publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 49 publications
5
91
1
1
Order By: Relevance
“…Overall, we detected at least three HRV-A and eight HRV-C types co-circulating in Tororo District. Of note, during the same collection period, a lethal HRV-C outbreak was reported in chimpanzees in Kibale National Park, in western Uganda [54]; that HRV-C was modestly related to an isolate observed in our study (74% nucleotide identity; 81% amino acid identity) (Fig 3) [54]. Our results confirm that a wide spectrum of HRVs infects Ugandan children.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, we detected at least three HRV-A and eight HRV-C types co-circulating in Tororo District. Of note, during the same collection period, a lethal HRV-C outbreak was reported in chimpanzees in Kibale National Park, in western Uganda [54]; that HRV-C was modestly related to an isolate observed in our study (74% nucleotide identity; 81% amino acid identity) (Fig 3) [54]. Our results confirm that a wide spectrum of HRVs infects Ugandan children.…”
Section: Discussionsupporting
confidence: 84%
“…Expression of the functional chimpanzee CMAH enzyme in cultured human cells resulted in comparable P. knowlesi invasion rates between human, chimpanzee, and macaque cells . Similar experiments targeting other pathogen‐interacting proteins that differ substantially among humans and nonhuman primates could be used to explore why other diseases that are deadly to humans but not nonhuman primates or vice versa (e.g., P. falciparum or rhinovirus, respectively) do not progress similarly across host species.…”
Section: Functional Genomics and Evolutionary Anthropologymentioning
confidence: 99%
“…From February to September 2013, three different phases of a rhinovirus C outbreak among the chimpanzee population appeared in Uganda. During this outbreak, five chimpanzees (one infant and four adults) died in a population of 56, representing an 8.9% mortality rate [73]. The autopsy of a dead infant chimpanzee revealed that the morphology of lung parenchyma was affected, with hepatic congestion and hepatomegaly.…”
Section: Ugandamentioning
confidence: 99%
“…The deep sequencing analysis found the sequences of rhinovirus C, which was further confirmed using real time RT-PCR. Interestingly, it was observed that the Kibale National Park where the community of these chimpanzees is based is usually visited by a number of tourists, researchers, and other local people living nearby the reserve, hence the possibility of transmission of the disease from contact appears to be the most likely transmission pathway [73].…”
Section: Ugandamentioning
confidence: 99%